Pediatric Cancer in Africa : A Case-Based Guide to Diagnosis and Management - Stefan, Daniela Cristina; Harif, Mhamed (Springer International Publishing : Imprint: Springer, 2017)
This text is the only book of its kind to provide specific guidance applicable to limited resource settings and builds up from the foundation of general practitioner or general pediatrician competence. Written and edited by leaders in the field, this manual educates physicians on the essential components of the discipline, filtered through the experience of specialists from developing countries, with immediate applicability in the specific healthcare environment in these countries. Typically, manuals of pediatric hematology-oncology are written by specialists from high-income countries, and usually target an audience with a sub-specialist level of training, often assisted by cutting-edge diagnostic and treatment facilities. However, approximately 80% of new cases of cancer in children appear in mid- and low-income countries. Almost invariably, general practitioners or general pediatricians without special training in oncology will look after children with malignancies who enter the health care system in these countries. The diagnostic facilities are usually limited, as are the treatment options. The survival figures in these conditions are somewhere below 20%, while in high-income countries they are in the range of 80% for many childhood cancers. This book includes simplified therapy protocols, pain therapy and palliation, as well as ward procedures such as bone marrow aspiration/biopsies, intravenous therapy and chemotherapy drugs mixing. It provides an overview of pediatric cancer epidemiology, cancer registration and organizing support networks and features the management of cancers with associated pathology like AIDS, malnutrition, malaria and tuberculosis.- Resumé vydavatel
Keywords: maligní nádorová onemocnění; děti; adolescenti; cancer; children; adolescents; Africa; elektronické knihy; monografie; electronic books; monographs